The links between the gut microbiome and non-alcoholic fatty liver disease (NAFLD) - Safari, Zahra; Gérard, Philippe (Cellular and molecular life sciences : CMLS, 2019)
NAFLD is currently the main cause of chronic liver disease in developed countries, and the number of NAFLD patients is growing worldwide. NAFLD often has similar symptoms to other metabolic disorders, including type 2 diabetes and obesity. Recently, the role of the gut microbiota in the pathophysiology of many diseases has been revealed. Regarding NAFLD, experiments using gut microbiota transplants to germ-free animal models showed that fatty liver disease development is determined by gut bacteria. Moreover, the perturbation of the composition of the gut microbiota has been observed in patients suffering from NAFLD. Numerous mechanisms relating the gut microbiome to NAFLD have been proposed, including the dysbiosis-induced dysregulation of gut endothelial barrier function that allows for the translocation of bacterial components and leads to hepatic inflammation. In addition, the various metabolites produced by the gut microbiota may impact the liver and thus modulate NAFLD susceptibility. Therefore, the manipulation of the gut microbiome by probiotics, prebiotics or synbiotics was shown to improve liver phenotype in NAFLD patients as well as in rodent models. Hence, further knowledge about the interactions among dysbiosis, environmental factors, and diet and their impacts on the gut–liver axis can improve the treatment of this life-threatening liver disease and its related disorders.